Characteristics of Learning in Islamic Boarding Schools - Saputra, Dedi; Warisno, Andi; Ansori, Afif; Andari, An An; Andayani, Sri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to describe the characteristics of learning in Islamic boarding schools. This research is qualitative with a literature approach. Research data is from learning characteristics in Islamic boarding schools with book and journal data sources. The collection technique is done by documentation. Meanwhile, data analysis uses content analysis. The study results show that the Islamic boarding school curriculum is more flexible. The curriculum is more oriented towards religious studies such as Nahwu, Sharaf, Ushul Fiqh, Mustalah Hadith, Tafsir, and Sufism. The curriculum in Islamic boarding schools is determined more by the kiai. Then the learning methods used in Islamic boarding schools include the band organ method, the slogan method, the discussion method, the rote method, the classical method, the demonstration method, the lecture method, and the question-and-answer method. Thus, Islamic boarding schools have different learning characteristics from other educational institutions.